Social media use, body image, and body weight status: comparison between university students with and without disordered eating in Universiti Putra Malaysia - Eow, Shiang Yen; Gan, Wan Ying (Community Health Society Malaysia, 2018)
Background: Disordered eating, body dissatisfaction, and social media use are increasingly common among university students. This cross-sectional study aimed to compare social media use, body image, and body weight status between disordered eating (DE) and non-disordered eating (NDE) university students. Materials and Methods: There were two phases of data collection. In Phase I, a total of 505 university students (22.6% males and 77.4% females) with a mean age of 21.26 ± 1.41 years from three randomly selected faculties in UPM were screened for disordered eating using the Eating Attitude Test (EAT-26). Sociodemographic background and anthropometric measurements including weight, height, waist circumference, and body fat percentage of respondents were measured. In Phase II, those respondents with DE were matched with those without DE by sex, age, and ethnicity. They answered an online survey on body image and social media use. Result: Out of 505 university students in Phase I, 21.8% were engaged in DE with no sex difference observed (χ2=0.738, p=0.390). In Phase II, 106 DE respondents were matched with 106 NDE respondents. No significant differences were found in body image, social media use (duration, volume, frequency, engagement, selfie sharing, photo investment, and photo manipulation) and body weight status between DE and NDE groups. However, DE respondents reported to have a significantly higher frequency of selfie-taking as compared to NDE respondents (t=-2.338, p=0.020). Conclusion: High prevalence of disordered eating was observed in this study. The contribution of social media use to disordered eating needs to be further studied.